2018
DOI: 10.1007/s00253-018-9225-9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and community structure of ammonia oxidizers in a marsh wetland of the northeast China

Abstract: As an interface of terrestrial and aquatic ecosystems, wetland is a hotspot of the global nitrogen cycle. Ammonia oxidation is an essential part of the nitrogen cycle and is conducted by ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB). Based on the amoA gene, the distribution and genetic diversity of AOA and AOB in the marsh wetland soil with different soil layers and vegetation had been investigated. The result showed that both soil layer and vegetation significantly influenced the divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In our study, long-term fertilization with inorganic fertilizers reduced the growth of AOA but increased the growth of AOB in black soil compared to that with organic fertilizers. This results was similar to the obvious research, which indicated that showed that chemical fertilizers can decrease the diversity of the AOA community 2 , 37 . Organic fertilizer provides a variety of inorganic and organic nutrients, such as organic acids, for crops while fertilizing the soil, maintaining soil pH and improving the soil structure and ecosystem 38 , 39 .…”
Section: Discussionsupporting
confidence: 90%
“…In our study, long-term fertilization with inorganic fertilizers reduced the growth of AOA but increased the growth of AOB in black soil compared to that with organic fertilizers. This results was similar to the obvious research, which indicated that showed that chemical fertilizers can decrease the diversity of the AOA community 2 , 37 . Organic fertilizer provides a variety of inorganic and organic nutrients, such as organic acids, for crops while fertilizing the soil, maintaining soil pH and improving the soil structure and ecosystem 38 , 39 .…”
Section: Discussionsupporting
confidence: 90%
“…In ocean, lake, and soil environments, the amoA gene copy numbers from AOA are tens or even thousands of times greater than those from AOB (Li, Weng, Huang, Su, & Yang, 2015). Studies have shown that AOA prefer areas with low ammonium concentrations, whereas AOB prefer areas with high ammonium concentrations (Gao, Liu, Li, Chen, & Liang, 2018a;Ouyang, Norton, & Stark, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In ocean, lake, and soil environments, the amoA gene copy numbers from AOA are tens or even thousands of times greater than those from AOB (Li, Weng, Huang, Su, & Yang, ). Studies have shown that AOA prefer areas with low ammonium concentrations, whereas AOB prefer areas with high ammonium concentrations (Gao, Liu, Li, Chen, & Liang, ; Ouyang, Norton, & Stark, ). When AOA and AOB coexist in most agricultural soils, they differ in terms of their responses to environmental disturbances (i.e., niche specialization) and resource utilization (i.e., niche differentiation) (Gao, Chang, et al, ; Ouyang, Norton, Stark, Reeve, & Habteselassie, ).…”
Section: Introductionmentioning
confidence: 99%